Psychological Mechanisms Of Aggressive Behavior In Teenagers - Isakovna, Kushanova Mashkhura; Yunusovich, Akhrorov Voris (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the concepts of aggression and aggressive behavior, the differences between them, the views of scientists who have conducted research in this field, their definitions and the rules developed. In today’s society, the issue of aggression is one of the most pressing issues in the field of psychology, the literature published in the field of psychology, scientific research. A description of this dangerous psychological condition is thought to be a set of individual or collective behaviors that result in physical and mental harm to individuals and groups of people.